O corpo nos laboratórios de liturgia da rede celebra. - Silva, Helio Soares da (2014)
The object of this work is the body in the laboratories of the liturgy celebrates Network. The study was conducted through literature research and participant observation. It was investigated whether the methods used in laboratories litírgicos actually ensure the full participation of the person in the liturgy; if the individuals involved acquire a more integrated and full perception of self and other, and how they acquire understanding of the cosmos. It was found that Network takes over the body as an element of capital importance for the completion of the rite, so she has sought, through the liturgy laboratories, working for those involved in liturgical action can be positioned fully in comprising this sense the rediscovery of corporeality. This effort has contributed to a better understanding of the human being in its entirety, where the individual perceives himself interacting with his peers, with the cosmos and with the transcendent.